HAS Should Not Be NICE: Rejecting Imaginary Worlds in the French Technology Assessment Guidelines - Paul C Langley (INNOVATIONS in Pharmacy, 2017)
Pricing decisions and access to pharmaceuticals should be evidence based. Unfortunately, the French guidelines for technology assessment, in their adoption of the National Institute for Health and Clinical Excellence (NICE) reference case modeling standard ensure that this is not the case. Rather than requiring the submission of claims that are credible, evaluable and replicable, the Haute Autorité de Sante (HAS) mandates the creation of imaginary worlds to support comparative effectiveness and cost-outcome claims. The purpose of this commentary is to make the case that HAS should reconsider this commitment to standards for health technology assessment that are more appropriately seen as pseudoscience. The recommendation is that HAS should put to one side mandating lifetime cost-per-quality adjusted life year (QALY) or life years saved claims in favor of short-term claims that can be evaluated and reported to health system decision makers as part of a provisional assessment of new products as well as supporting ongoing disease area and therapeutic class reviews.